Urethral length and bladder neck behavior: can dynamic magnetic resonance imaging give the same results as introital ultrasound? - Alt, Céline D.; Hallscheidt, Peter; Sohn, Christof; Kauczor, Hans-Ulrich; Eickhoff, Simon B.; Brocker, Kerstin A. (Archives of gynecology and obstetrics, 2019)
PurposeTo compare dynamic magnetic resonance imaging (dMRI) and introital ultrasound results with regard to urethral length measurements and the evaluation of bladder neck changes.MethodsRetrospective analyses of urethral length measurements and detection of bladder neck changes (rotated/vertical bladder neck descent, urethral funneling) were conducted in women—scheduled for surgical treatment with alloplastic material—who had undergone introital ultrasound and dMRI presurgery and 3 months postsurgery. Measurement differences between both imaging modalities were evaluated by assessing the confidence interval for the difference in means between the datasets using bootstrap analysis.ResultsBased on data from 40 patients (320 image series), the urethra could be clearly measured on every pre- and postsurgical dMRI dataset but not on preoperative ultrasound images in nine women during Valsalva maneuver due to a large cystocele. The estimation of the mean difference distribution based on 500,000 bootstrap resamples indicated that the urethral length was measured shorter by dMRI pre- and postsurgery at rest and postsurgery during Valsalva maneuver (median 1.6-3.1 mm) but longer by dMRI (median 0.2 mm) during Valsalva maneuver presurgery. Rotated/vertical bladder neck descent and urethral funneling diagnoses showed concordance of 67-74% in the direct comparison of patients; the estimation of the concordance indicated poorer outcomes with 50-72%.ConclusionsMetric information on urethral length from dMRI is comparable to that from introital ultrasound. dMRI is more advantageous in cases with an extended organ prolapse. At present, dMRI does not give the same diagnosis on bladder neck changes as introital ultrasound does.